Architectural investigation of wooden-pillared Konya Hatip Mosque - Bademci, Fikret (REIA - Revista Europea de Investigación en Arquitectura, 2023)
Wooden-pillared mosques are considered an important element of Turkish-Islamic architecture. Wooden-pillared mosques, which are generally found in Central Anatolia, have many architectural features. The materials used in the construction of these mosques are obtained from local sources, the construction techniques are traditional, and the designs are appropriate to the local culture. The ornaments on the building elements and the advanced level of woodwork are other factors that make this type of buildings valuable. However, there are serious problems regarding the preservation and maintenance of mosques with wooden pillars. Since wooden pillars are a natural material, they are likely to be exposed to decay, worms, and other environmental factors. Due to the difficulties in their preservation, the documentation of such structures plays an important role in transferring them to the future. The aim of the study is to architecturally analyze Konya Hat1p Mosque, one of the few historical wooden-pillared mosques, and to document its current condition. In this context, the building's literature was reviewed. In addition, the construction technique, material, decorations, and architectural elements of the building were examined and documented with photographs.